Peningkatan Kemampuan Sains Melalui Sentra Bahan Alam - Ayu Lestari (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2019)
Subject this research were seventeen students in kindergarten Nurul Huda Malang. This research refers to research methods Kemmis & Taggart models with one cycle of three meetings. Quantitative data is the result of the study shows that the development of science skills were statistically analyzed descriptively. The result is a process of learning science through learning strategy centers of natural ingredients can indicate the presence of seven components of scientific processes include observing, comparing, classifying, measuring, making simple inferences and predict and centers of learning strategies can improve the ability of natural materials science learners from meeting to 1 to meeting to 3 with an average 2.60 respectively; 2.70, and 2.99 in the growing category of learners and also increased the percentage of completeness of meetings to 1 to 3 to the meeting in a row with a value of 52.9%; 76.4% and 100%.